The Juscelino Kubitschek government and the Brazilian Malaria Control and Eradication Working Group: collaboration and conflicts in Brazilian and international health agenda, 1958-1961 - Renato da Silva; Carlos Henrique Assunção Paiva (História, Ciências, Saúde: Manguinhos, 2015)
Malaria, a disease which was under control in the beginning of Juscelino Kubitschek government, became the most important endemic disease in 1958, when Brazil made a commitment with the World Health Organization to convert its control programs into eradication programs. For this purpose a Malaria Control and Eradication Group was set up under the leadership of the malaria specialist Mário Pinotti. Malaria would become an important bargaining chip in the context of the development policies of Kubitschek. This article focuses on path of the Malaria Control and Eradication Working Group in Brazil, in its varying relationships with the arguments and guidelines established at international level